STOCHASTIC AND DETERMINISTIC METHODS IN THE ANALYSIS OF THE δ18O RECORD IN THE CORE V28-239 - Giese H.J.; Albeverio S.; Stabile G. (My University, 1999)
The paper discusses and compares application of several stochastic and deterministic methods for analysis of geological time-series, taking the δ18O record of the Pacific core V28-239 as a test object. The stochastic techniques include finite parameter linear models, such as ARMA and ARIMA, while the deterministic chaos approach deals with the Lyapunov exponent and correlation dimension, utilizing the Wolf algorithm and the Grassberger-Procaccia procedure, respectively. Neither stochastic nor deterministic models lead to definitive and unique conclusions. This is true for our results as well as for those of the previous authors obtained on the same dataset. The major limitations are the small size of the sample set and the uncertainties in assigned ages for the δ18O values. It may be that the emerging nonlinear stochastic techniques prove to be more suitable for treatment of geological time-series.
Keywords: STOCHASTIC AND DETERMINISTIC METHODS; TIME-SERIES; δ18O; PACIFIC CORE